2017
DOI: 10.1007/s10103-017-2178-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of radiant heat on conventional glass ionomer cements during setting by using a blue light diode laser system (445 nm)

Abstract: The aim of this in vitro study was to evaluate the effect of radiant heat on surface hardness of three conventional glass ionomer cements (GICs) by using a blue diode laser system (445 nm) and a light-emitting diode (LED) unit. Additionally, the safety of the laser treatment was evaluated. Thirty disk-shaped specimens were prepared of each tested GIC (Equia Fil, Ketac Universal Aplicap and Riva Self Cure). The experimental groups (n = 10) of the study were as follows: group 1 was the control group of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 20 publications
5
19
1
1
Order By: Relevance
“…This is in agreement with previous studies which investigated the effect of radiant heat treatments on surface hardness of GIC materials [8,9,11,12,15]. Thermal energy providing by the LED light-curing unit increased surface hardness of the tested GIC materials by thermocatalysis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with previous studies which investigated the effect of radiant heat treatments on surface hardness of GIC materials [8,9,11,12,15]. Thermal energy providing by the LED light-curing unit increased surface hardness of the tested GIC materials by thermocatalysis.…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies various techniques have been suggested in order to increase the surface hardness of the GIC 2 Advances in Materials Science and Engineering materials, which include radiant heat transfer by use of dental light-curing units such as light emitting diodes (LEDs) [9][10][11] or lasers [12], ultrasonic energy transfer to enhance the motivation and interaction of the reacted components of the GIC [9,13,14], and application of calcium chloride (CaCl 2 ) solutions in order to enhance the acid-base reaction between carboxylate groups (-COO − ) of the polyalkenoic acids and calcium cations (Ca +2 ) of the glass particles of the cement [15,16]. Among the above techniques the most common one for improving the physical and mechanical properties of the GIC materials is the radiant heat treatment using dental LED curing units.…”
Section: Introductionmentioning
confidence: 99%
“…There are previous studies that demonstrated increase in surface hardness [15,16], compressive strength [6] and abrasion resistance [19], as well as decrease in solubility and water sorption [20] of various GIC restoratives after radiant heat treatments with LED or laser (diode -445 nm) units. Furthermore, the safety of these treatments on the surface of the restorations (surface morphology and roughness) [13,20] and as regards with the pulp temperature rise [12,13], has been confirmed. On the other hand, it has been reported decrease in fluoride release after the radiant heat treatment due to the improvement of the setting reaction of the GICs and their decrease in solubility [11,16].…”
Section: Editorialmentioning
confidence: 80%
“…The final material consists of unreacted glass particles and a poly-salt matrix with cross-link bonds [10]. In previous studies various techniques have been suggested in order to improve the physical and mechanical properties of the conventional GICs, which include radiant heat transfer by use of dental light-curing units such as light emitting diodes (LEDs) [6,11,12] or lasers [13], ultrasonic energy transfer to enhance the motivation and interaction of the reacted components of the GIC [11,14,15] and application of calcium chloride (CaCl 2 ) solutions in order to enhance the acidbase reaction between corboxylate groups (-CΟΟ -) of the polyalkenoic acids and calcium cations (Ca +2 ) of the glass particles of the cement [16,17].…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation